On Generalized Absolute Matrix Summability of Infinite Series - í–zarslan, Hikmet S.; Karakaş, Ahmet (Communications in Mathematics and Applications, 2019)
In this paper, we have generalized a known theorem on \(|\bar{N},p_n|_{k}\) summability factors of infinite series with a new summability method by using almost increasing sequences. This new theorem also includes several new and known results.